2002
DOI: 10.1109/tns.2002.1039570
|View full text |Cite
|
Sign up to set email alerts
|

SIC: an intracerebral radiosensitive probe for in vivo neuropharmacology investigations in small laboratory animals: prototype design, characterization, and in vivo evaluation

Abstract: Several high-resolution tomographs dedicated to small animal imaging are presently under development. However, these devices are limited by two major drawbacks: their cost is high and they require animal anaesthesia and immobilization, thus restricting the scope of investigations. Therefore, we have developed SIC (French acronym for "Sonde IntraCérébrale") a low-cost beta microprobe for measuring local radioactivity in awake, freely moving animals. Besides good sensitivity, SIC offers the advantage of a high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…System dead time ͑2.5 s͒ was similar to that reported by Pain et al 28 and by Wollenweber et al 31 Because the system response did not reach a ceiling ͑the system did not saturate͒, it can be readily corrected to linear response over the range of radioactivity anticipated ͑R 2 = 0.999͒. Based on these data, this system can be used for accurately determining activity concentrations at least as high as 21.0 MBq/ ml.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…System dead time ͑2.5 s͒ was similar to that reported by Pain et al 28 and by Wollenweber et al 31 Because the system response did not reach a ceiling ͑the system did not saturate͒, it can be readily corrected to linear response over the range of radioactivity anticipated ͑R 2 = 0.999͒. Based on these data, this system can be used for accurately determining activity concentrations at least as high as 21.0 MBq/ ml.…”
Section: Discussionsupporting
confidence: 71%
“…This means that a measured energy spectrum of 15 O is quite different from that theoretically calculated by Champion and Loirec. 30 Moreover, our value is also about 18% above the average kinetic energy ͑492 keV͒ estimated by Monte Carlo simulation of Pain et al 28 using detection radius to detect 90% of positron particles emitted near the probe.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The limited range of b-particles within biological tissues leads to a limited detection volume centered around the scintillating tip of the probe. Monte Carlo simulations demonstrated that for C-11 the distance required to detect 90% of the b-particles around the probe is 2.0 mm (Pain et al, 2002). The sensitivity of the used b-scintillator was in the range of 0.036 to 0.047 cps/kBq/cc.…”
Section: B-scintillatormentioning
confidence: 99%
“…Most of these small sized dosimeters are devoted to conventional photon therapy, as those presented by Beddar et al, for use in stereotactic radiosurgery [5][6], or by Fontbonne et al for use in brachyterapy [7]. Pain et al have also presented a dosimeter allowing in vivo measurements of low dose β emission [8][9]. The potential use of plastic scintillators for the dosimetry in hadrontherapy has only been demonstrated for protons by Torissi [10].…”
Section: Introductionmentioning
confidence: 99%